Investigation on the Differential Quadrature Fabry–Pérot Interferometer with Variable Measurement Mirrors - Yi-Chieh Shih; Pi-Cheng Tung; Wen-Yuh Jywe; Chung-Ping Chang; Lih-Horng Shyu; Tung-Hsien Hsieh (Applied Sciences, 2020)
Due to the common path structure being insensitive to the environmental disturbances, relevant Fabry–Pérot interferometers have been presented for displacement measurement. However, the discontinuous signal distribution exists in the conventional Fabry–Pérot interferometer. Although a polarized Fabry–Pérot interferometer with low finesse was subsequently proposed, the signal processing is complicated, and the nonlinearity error of sub-micrometer order occurs in this signal. Therefore, a differential quadrature Fabry–Pérot interferometer has been proposed for the first time. In this measurement system, the nonlinearity error can be improved effectively, and the DC offset during the measurement procedure can be eliminated. Furthermore, the proposed system also features rapid and convenient replacing the measurement mirrors to meet the inspection requirement in various measuring ranges. In the comparison result between the commercial and self-developed Fabry–Pérot interferometer, it reveals that the maximum standard deviation is less than 0.120 μm in the whole measuring range of 600 mm. According to these results, the developed differential Fabry–Pérot interferometer is feasible for precise displacement measurement.